Midnight for Charlie Bone / 1. - Nimmo, Jenny (Children of the red king, 2003)
Charlie doesn't want to believe it when he discovers that he can hear the thoughts of people in photographs. But his horrible aunts are delighted. It means that he is one of the chosen and must attend the Bloor's Academy for gifted children. Once there, Charlie realizes that some of his classmates have equally mysterious powers, and soon Charlie is involved in uncovering the mysterious past of one of them.